Epigenetic alterations in Sjögren’s syndrome patient saliva - Karagianni, P. (Clin Exp Immunol, 2020)
Epigenetic mechanisms have been implicated in the pathogenesis of Sjögren’s syndrome (SS). Extensive alterations in DNA methylation have been described in minor salivary gland (MSG) epithelial cells and lymphocytes derived from SS patients compared to sicca controls. In an effort to identify novel potential epigenetic markers that could prove useful in diagnosis and disease monitoring, we explored whether DNA methylation differences can also be detected in saliva from SS patients compared to sicca controls. We performed DNA methylation analysis by methylation‐sensitive restriction digestion followed by quantitative real‐time polymerase chain reaction of selected genomic loci in saliva samples of 16 SS patients and 10 sicca controls with negative MSG biopsy. We identified reduced DNA methylation of the imprinting control region (ICR) of the H19 locus in SS patient saliva compared to sicca controls. Levels of saliva H19 ICR methylation were negatively correlated with C4 serum complement levels. Consistent with the reduced methylation of the ICR, H19 RNA levels were increased in SS patient peripheral blood mononuclear cells (PBMCs), while no significant change was observed in MSG H19 RNA levels compared to sicca controls. Our findings support that H19 ICR methylation could be a useful molecular epigenetic marker in monitoring patients with SS, highlighting saliva as a valuable biological sample in SS research and clinical practice. The role of H19 in SS pathogenesis remains to be addressed.